DZIELIMY SIĘ DOŚWIADCZENIEMIntra-myocardial right ventricular haemangioma in combination with a coronary fistula - Babin-Ebell, Jörg; Froehner, Steffen; Neophytou, Ioannis; Urbanski, Paul; Diegeler, Anno (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Cardiac haemangiomas are rare benign neoplasms of the heart. Though co-existing lesions have been described before, the present case is the first to report an intra-myocardial right ventricular haemangioma in combination with a coronary fistula and tricuspid regurgitation.